### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The cubic equation with roots 2, -1, and 1 has coefficients 1, -2, -3, and 2.

To find the coefficients of a cubic equation with given roots, we start with the factored form of the equation:

(x - r1)(x - r2)(x - r3) = 0

where r1, r2, and r3 are the roots. Expanding this expression gives:

x^3 - (r1 + r2 + r3)x^2 + (r1r2 + r1r3 + r2r3)x - r1r2r3 = 0

Comparing this to the standard form of a cubic equation:

ax^3 + bx^2 + cx + d = 0

we can see that the coefficients are related to the roots by:

a = 1

b = -(r1 + r2 + r3)

c = r1r2 + r1r3 + r2r3

d = -r1r2r3

Substituting the given roots into these formulas, we get:

a = 1

b = -(2 + (-1) + 1) = -2

c = 2(-1)(1) + 2(2)(1) + (-1)(1) = -2

d = -(2)(-1)(1) = 2

Therefore, the coefficients of the cubic equation with roots 2, -1, and 1 are 1, -2, -3, and 2. The equation can be written as:

x^3 - 2x^2 - 3x + 2 = 0

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...